Yugen Aesthetic Element in Japanese Animation - F Febrianty; F Fauziyah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Yugen is an artistic aesthetic as a combination of elements of seijaku (silent), yojo (lasting impression), muhyojo (expressionless), and aki (emptiness). In general, yugen means mysterious beauty, where a beauty can only be felt in an object, even though that beauty does not exist in the true sense of the word and cannot be seen directly. Yugen became one of the characteristics of Japanese literature. Hakkeden Touhou Hakken Ibun (2013) by Abe Miyuki is a anime that contains elements of yugen. This anime is an adaptation of a yomihon (novel) entitled Satomi Hakkenden, the masterpiece of Takizawa Bakin who was a great Japanese writer at the end of premodern Japan. This study aims to analyze the yugen element in the Hakkeden Touhou Hakken Ibun anime. This research is a library research with an objective approach. The research method used is descriptive analysis. Yugen aesthetics in anime are visualized in such a way as to invite the audience to imagine in such a way that they can find and feel the beauty that exists. The concept of beauty like this is one of the characteristics of Japanese literature, including anime. In this study, it can be concluded that in the Hakkeden Touhou Hakken Ibun anime, there is a yugen aesthetic by highlighting the dominance of dark colors. But that doesn't mean that the dominance of dark colors gives a strong or fearful impression, but that dark colors can also create a sense of calm, comfort, security. And, by combining elements with one another, this dark color can give meaning, loneliness, and solitude.